Perbandingan Hasil Forensics Jaringan Terhadap Serangan E-mail Spamming dan Spoofing - Fitriyani Tella; Imam Riadi; Sunardi . (Fakultas Ilmu Komputer, 2020)
Abstract In the era of technology, email has become one of the important things in the means of communication. Email is a medium for communication and also a place to store crime. One common crime is email spamming and spoofing. Spam is junk mail or unwanted messages, this spam email will be sent to someone's inbox and is useless to the recipient. Spam is sent on the network to increase network traffic. Email spoofing is a way to hide the origin of messages used by spammers. Email spoofing can change the email sender's information ie in the